KONTRIBUSI MATHEMATICS ANXIETY TERHADAP KEMAMPUAN AKADEMIK MAHASISWA PADA PEMBELAJARAN KALKULUS - Hidayat, Rifqi; Rahmatudin, Jajang (Sains and Technology Faculty, Walisongo State Islamic University, 2018)
This reseach comprehending on the relation between mathematics anxiety and the academic competence of the first level students. This research is constituted by the performance of most students of the early study program of mathematics education still feel anxiety when dealing with mathematical problems in the learning of calculus, the emerging discomfort felt by the students. The method of this research is survey with corelation technique. The use of this method is to see how strong and how far the influence of mathematics anxiety on the students academic competence. The population of this research is the students of Mathematics Department faculty of teacher training and education in Muhammadiyah University of Cirebon in the academic year 2016/2017. The sample of the research is purposive sampling which consists of 20 students who contracted differential calculus subject. The instrument used in this research is mathematics anxiety scala. The result of the research shows that there is a negative relation between mathematics anxiety and students’ academic competence. The mathematics anxiety gives a contribution 35% to the students’ academics competence, and 65% influenced by other factors not examined in this study.